Anodic bonding driven by the pulse current signal of triboelectric nanogenerator. (July 2020) - Lin, Yuxing; Nie, Jinhui; Bai, Yu; Li, Shuyao; Xu, Liang; Wang, Fan; Ding, Yafei; Tian, Jingwen; Li, Yufang; Chen, Xiangyu; Shen, Honglie
Abstract: Anodic bonding technique has been extensively utilized in the micro-electromechanical systems (MEMS) packaging or solar cell sealing. Nevertheless, the traditional power source for bonding method needs both high voltage and high current, which limits the widespread applications of anodic bonding and also gives rise to energy consumption. Therefore, for the first time, triboelectric nanogenerator (TENG) is used to drive anodic bonding. The TENG-based Anodic bonding system features lower current and much less transferred charges requirement, while no pre-tensile strength of the bonded pairs is needed to achieve completed bonding. Under the drive of TENG, the silicon-glass interface with the size of 100 mm 2 can be tightly bonded within 40 s, which is comparable with the results driven by commercial power source. In addition, triple-stack anodic bonding driven by TENG through a two-step bonding process can be realized effectively with good reliability. This TENG-based Anodic bonding system with simple design and zero power consumption can significantly improve applications of anodic bonding in many fields, while it also opens up a promising utilization direction of the current signal of TENG. Graphical abstract: Image 1 Highlights: For the first time, Triboelectric nanogenerator (TENG) has been used to directly drive silicon-glass anodic bonding. The TENG-based Anodic bonding system develops a new approach for utilizing the current signal from TENG. For the same bonding area, TENG-based Anodic bonding system needs 19% of transferred charges of that driven by power source. The TENG-based Anodic bonding has potential applications for MEMS packing and sensor fabrication.